MULTI-FREQUENCY RADIO INTERFEROMETRY ALGORITHM - Orlov, V. V.; Lytvynenko, O. A.; Galanin, V. V, (Одеські астрономічні публікації, 2019)
This article is a continuation of the work published in (Orlov, 2018). A method of multi-frequency beamforming of a radio interferometer is proposed. The model diagram is presented, which consists of two antenna arrays, filters, receivers and a signal summing circuit. The model works as follows. The signals received by the antennas pass through the narrow-band filters of the receiving devices, which are tuned to certain frequencies, after which they are subjected to multiplicative processing and weighted summation with their coefficients. In this work, model the system of a radio interferometer based on multi-frequency signal processing, and study the possibilities of minimizing the level of side lobes of the antenna pattern (AP). It is shown that a decrease in the level of side lobes is possible due to the expansion of the frequency range or the application of signal processing from several clusters (antenna arrays), due to their summation in the interferometer circuit. For the case of three bases of the interferometer, consisting of the same antenna arrays, the total AP is calculated. In this case, a significant reduction of the side lobes to the level of the side lobes of a single antenna array is achieved. Further optimization of the radiation pattern can be carried out by choosing the frequency ranges of the interferometers and weights when summing the signals. The proposed method makes it possible to adapt the interferometer AP due to time processing in frequency channels. The choice of the frequency grid and weighted multi-frequency signal processing provide a decrease in the level of side lobes and increase the resolution of the instruments. The application of the proposed algorithms will reduce the confusion effect from closely spaced radio sources. The computational possibilities of weighted processing are realized in real time, taking into account the rotation of the Earth, scanning the AP and angular arrangement of radio sources.